Karakteristik Rasm Dan Sumber Penafsiran Al-Qur’an - Nurul Istiqomah (QOF, 2022)
The use of the digital Qur'an is growing rapidly in the midst of society. The emergence of the digital Qur'an makes it easier for people to access the Qur'an by simply opening it from their mobile phone. This requires attention from academics, especially in the fields of the Qur'an and interpretation. In Indonesia, there are already agreed standard manuscripts, namely mus}haf bahriyyah dan mus}h{af bombay manuscripts. Both manuscripts follow the rules of the Ottoman Empire. In this study, we will analyze the rasm and sources of interpretation used by one of the digital applications, namely the Qur'an (free). The aim is to describe the characteristics of this application. This research is a type of library research. The method used is a qualitative method. This study will compare the rasm in the application of the Qur'an (free) with some authoritative data regarding the Ottoman theory of race and those related to standardization theory prevailing in Indonesia. The results of this study are the application of the Qur'an (free) following the Ottoman Empire. Furthermore, the source of interpretation used in this application is al-Muntakhab fi> tafsi>r al-Qur’a>n al-kari>m which is the interpretation of the ministry of religion in Egypt.